Fabrication and sustained release properties of poly(epsilon-caprolactone) electrospun fibers loaded with layered double hydroxide nanoparticles intercalated with amoxicillin - Malagon Aviles, O. (2012)
Amoxicillin (AMOX) was intercalated in layered double hydroxide (LDH) nanoparticles by coprecipitation. LDH intercalated with AMOX (LDH/AMOX) was successfully encapsulated at different concentrations into poly(?-caprolactone) (PCL) by the electrospinning technique. Mats of non-woven PCL fibers loaded with LDH/AMOX were obtained and characterized in terms of morphology and in vitro release. The fibrous structure of a pristine PCL sample was composed of individual, uniform, and randomly oriented fibers with an average diameter ranging around 0.8. ?m. The addition of LDH/AMOX at different concentrations caused a slight increase of the average diameter and the presence of rare beads possibly due to clusters of the nano-hybrid on the surface of the microfibers.The release curves present a sustained release behavior, although an initial rapid drug release was found. The initial high-rate drug release period was followed by a second step in which the release is slow, extending for long time. The comparison of the release curves showed that the release of AMOX protected into the clay is slower than the release of the drug alone. © 2012 Elsevier B.V.